Quality of life of primary brain tumor patients before and 3 months after discharge from a hospital in Bandung, Indonesia - Ganefianty, Amelia; Kariasa, I Made; McAllister, Susan; Fahmi, Ismail; Sarjono, Kalih; Faried, Ahmad; Sutiono, Agung B; Derrett, Sarah (Makara Journal of Health Research, 2019)
Background: The quality of life of patients with primary brain tumor in Indonesia is poorly understood. Therefore, this study aimed to investigate the health‐related quality of life of patients admitted to the Neurosurgery Department of Dr. Hasan Sadikin Hospital, Bandung, Indonesia, up to 3 months after discharge. Methods: Baseline data were collected from patients aged ≥18 years who were admitted to the hospital between October 9, 2015, and February 17, 2016. In‐person interviews were then conducted 1–2 days pre‐discharge (n = 65) and follow-up telephone interviews were made 1, 2, and 3 months post-discharge (n = 58, 55, and 54, respectively) to collect socio-demographic data, clinical characteristics, and EQ‐5D‐5L data. Results: Prior to discharge, one‐third or less of the 65 patients interviewed reported “no problems” with mobility (32%), self‐care (32%), usual activities (18%), and pain/discomfort (43%), whereas 74% reported “no problems” with anxiety/depression. By contrast, at 3 months post-discharge, an increased proportion of patients reported “no problems” with mobility (61%), self‐care (67%), usual activities (56%), and pain/discomfort (76%), with little change in anxiety/depression (“no problems” 70%). Conclusions: While there was improvement, many patients were still reporting problems at 3 months post-discharge, highlighting the need for ongoing support and care to ensure the best possible outcomes.